me ajuda por favor gente
Anexos:
![](https://pt-static.z-dn.net/files/d17/feb19258361ef7f74df6ce58028f488b.jpg)
Soluções para a tarefa
Respondido por
1
6 -
a)![(7-x)^2 = 7^2 - 2\cdot7\cdot x + x^2 = 49 - 14x + x^2 (7-x)^2 = 7^2 - 2\cdot7\cdot x + x^2 = 49 - 14x + x^2](https://tex.z-dn.net/?f=%287-x%29%5E2+%3D+7%5E2+-+2%5Ccdot7%5Ccdot+x+%2B+x%5E2+%3D+49+-+14x+%2B+x%5E2)
b)![(4y - 5)^2 = (4y)^2 - 2\cdot 4y\cdot 5 +(-5)^2 = 16y^2 - 40y + 25 (4y - 5)^2 = (4y)^2 - 2\cdot 4y\cdot 5 +(-5)^2 = 16y^2 - 40y + 25](https://tex.z-dn.net/?f=%284y+-+5%29%5E2+%3D+%284y%29%5E2+-+2%5Ccdot+4y%5Ccdot+5+%2B%28-5%29%5E2+%3D+16y%5E2+-+40y+%2B+25)
7 -
a)![(2x - 5)(2x + 5) = (2x)^2 - (5)^2 = 4x^2 - 25 (2x - 5)(2x + 5) = (2x)^2 - (5)^2 = 4x^2 - 25](https://tex.z-dn.net/?f=%282x+-+5%29%282x+%2B+5%29+%3D+%282x%29%5E2+-+%285%29%5E2+%3D+4x%5E2+-+25)
b)![(y + 10)(y - 10) = y^2 - (10)^2 = y^2 - 100 (y + 10)(y - 10) = y^2 - (10)^2 = y^2 - 100](https://tex.z-dn.net/?f=%28y+%2B+10%29%28y+-+10%29+%3D+y%5E2+-+%2810%29%5E2+%3D+y%5E2+-+100)
8 -
b)![302^2 = 302^2 =](https://tex.z-dn.net/?f=302%5E2+%3D+)
![302^2 = (310 - 8)^2 = 310^2 - 2\cdot310\cdot8 + (- 8^2) = 96100 - 4960 + 64 = 91204 302^2 = (310 - 8)^2 = 310^2 - 2\cdot310\cdot8 + (- 8^2) = 96100 - 4960 + 64 = 91204](https://tex.z-dn.net/?f=302%5E2+%3D+%28310+-+8%29%5E2+%3D+310%5E2+-+2%5Ccdot310%5Ccdot8+%2B+%28-+8%5E2%29+%3D+96100+-+4960+%2B+64+%3D+91204)
c)![49^2 49^2](https://tex.z-dn.net/?f=49%5E2)
![49^2 = (50 - 1)^2 = 50^2 - 2\cdot 50\cdot1 = 1^2 = 2500 - 100 + 1 = 2401 49^2 = (50 - 1)^2 = 50^2 - 2\cdot 50\cdot1 = 1^2 = 2500 - 100 + 1 = 2401](https://tex.z-dn.net/?f=49%5E2+%3D+%2850+-+1%29%5E2+%3D+50%5E2+-+2%5Ccdot+50%5Ccdot1+%3D+1%5E2+%3D+2500+-+100+%2B+1+%3D+2401)
d)![2002\cdot198 = (200 + 2)(200 - 2) = 200^2 - 2^2 = 40000 - 4 = 39996 2002\cdot198 = (200 + 2)(200 - 2) = 200^2 - 2^2 = 40000 - 4 = 39996](https://tex.z-dn.net/?f=2002%5Ccdot198+%3D+%28200+%2B+2%29%28200+-+2%29+%3D+200%5E2+-+2%5E2+%3D+40000+-+4+%3D+39996)
9 -
a) Fator comum: 3; fatoração: 3(a + bc) = 3a + 3bc
b) Fator comum: 4y; fatoração: 4y(x + 3) = 4xy + 12y
10 -
a) 12x - 4y + 3xz - yz = 4(3x - y) + z(3x - y) = (3x - y)(4 + z)
b) ax + ay + bx + by = a(x + y) + b(x + y) = (x + y)(a + b)
11 -
a)![25 - b^2 25 - b^2](https://tex.z-dn.net/?f=25+-+b%5E2)
![25 - b^2 = (5 - b)(5 + b) 25 - b^2 = (5 - b)(5 + b)](https://tex.z-dn.net/?f=25+-+b%5E2+%3D+%285+-+b%29%285+%2B+b%29)
b)![x^4 - 16y^2 x^4 - 16y^2](https://tex.z-dn.net/?f=x%5E4+-+16y%5E2)
![x^4 - 16y^2 = (x^2 + 4y)(x^2 - 4y) x^4 - 16y^2 = (x^2 + 4y)(x^2 - 4y)](https://tex.z-dn.net/?f=x%5E4+-+16y%5E2+%3D+%28x%5E2+%2B+4y%29%28x%5E2+-+4y%29)
12 -
a)
= ![(x + 1)^2 = x^2 + 2\cdot x\cdot1 + 1^2 = x^2 + 2x + 1 (x + 1)^2 = x^2 + 2\cdot x\cdot1 + 1^2 = x^2 + 2x + 1](https://tex.z-dn.net/?f=%28x+%2B+1%29%5E2+%3D+x%5E2+%2B+2%5Ccdot+x%5Ccdot1+%2B+1%5E2+%3D+x%5E2+%2B+2x+%2B+1)
b)
= ![(b - 4)^2 = b^2 -2\cdot b\cdot4 = b^2 - 8b + 16 (b - 4)^2 = b^2 -2\cdot b\cdot4 = b^2 - 8b + 16](https://tex.z-dn.net/?f=%28b+-+4%29%5E2+%3D+b%5E2+-2%5Ccdot+b%5Ccdot4+%3D+b%5E2+-+8b+%2B+16)
c)
= ![(m + 6)^2 = m^2 + 2\cdot m\cdot6 + 6^2 = m^2 + 12m + 36 (m + 6)^2 = m^2 + 2\cdot m\cdot6 + 6^2 = m^2 + 12m + 36](https://tex.z-dn.net/?f=%28m+%2B+6%29%5E2+%3D++m%5E2+%2B+2%5Ccdot+m%5Ccdot6+%2B+6%5E2+%3D+m%5E2+%2B+12m+%2B+36)
Espero ter ajudado muitíssimo.
a)
b)
7 -
a)
b)
8 -
b)
c)
d)
9 -
a) Fator comum: 3; fatoração: 3(a + bc) = 3a + 3bc
b) Fator comum: 4y; fatoração: 4y(x + 3) = 4xy + 12y
10 -
a) 12x - 4y + 3xz - yz = 4(3x - y) + z(3x - y) = (3x - y)(4 + z)
b) ax + ay + bx + by = a(x + y) + b(x + y) = (x + y)(a + b)
11 -
a)
b)
12 -
a)
b)
c)
Espero ter ajudado muitíssimo.
alvaroamitai12:
(14 - y)2 = 196 - 28y + y2
Perguntas interessantes
Ed. Física,
9 meses atrás
Matemática,
9 meses atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Português,
1 ano atrás